Using Pictures to Improve Students’ Writing Skill at SMPN 3 Sungai Pua - Diana Putri (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2020)
The purpose of this study was to improve students' skills in writing using pictures for grade VII 1 and VII 2 students at SMP N 3 Sungai Pua in the academic year 2020/2021. This research is an action research. Research members consisted of researchers, English teachers, and class VII 1 , VII 2 students. The research was conducted in two cycles. The steps include reconnaissance, planning, action and observation, and reflection. This research data is qualitative in nature supported by quantitative data. Qualitative data were obtained by observing the teaching and learning process and interviews with English teachers and students VII 1 and VII 2. Qualitative data in the form of field notes and interview transcripts which were analyzed based on qualitative data analysis. Pre-test and post-test were conducted to obtain quantitative data. To analyze quantitative data in the form of students' writing scores, the pre-test and post-test scores were used. The findings show that pictures effectively improve students' skills in writing English. These improvements include: 1) students perceive writing as an easy and interesting lesson, which is shown by their enthusiasm for writing, 2) students are more likely to generate and organize ideas in an orderly manner, 3 ) pictures improve students' writing skills. Researchers found that students' writing skills improved. This can be seen from the main scores of the pre-test and post-test. There was an increase between the pre-test mean (77.6) and the post-test mean (97.07). So it can be concluded that the use of pictures can improve English writing skills.